"Association of MTHFR and MS/MTR gene polymorphisms with congenital heart defects in North Indian population (Jammu and Kashmir): a case-control study encompassing meta-analysis and trial sequential analysis" - Jyotdeep Kour Raina; Rakesh Kumar Panjaliya; Vikas Dogra; Sushil Sharma; Anupriya; Parvinder Kumar (BMC, 2022)
Abstract Background The risk of Congenital Heart Defects (CHD) is greatly influenced by variants within the genes involved in folate-homocysteine metabolism. Polymorphism in MTHFR (C677T and G1793A) and MS/MTR (A2756G) genes increases the risk of developing CHD risk, but results are controversial. Therefore, we conducted a case-control association pilot study followed by an up-dated meta-analysis with trial sequential analysis (TSA) to obtain more precise estimate of the associations of these two gene variants with the CHD risk. Methods For case-control study, we enrolled 50 CHD patients and 100 unrelated healthy controls. Genotyping was done by PCR-RFLP method and meta-analysis was performed by MetaGenyo online Statistical Analysis System software. For meta-analysis total number of individuals was as follows: for MTHFR C677T 3450 CHD patients and 4447 controls whereas for MS A2756G 697 CHD patients and 777 controls. Results Results of the original pilot study suggested lack of association for MTHFR C677T and MS A2756G polymorphism with risk of CHD whereas MTHFR G1793A was significantly associated with the disease. On performing meta-analysis, a significant association was observed with MTHFR C677T polymorphism but not with MS A2756G. Trial sequential Analysis also confirmed the sufficient sample size requirement for findings of meta-analysis. Conclusions The results of the meta-analysis suggested a significant role of MTHFR in increased risk of CHD.